Research on The Mechanical State Parameter Extraction Method of High Voltage Circuit Breakers - Yang Tianxu; Wang jianwei; Hu Xiaoguang (Institute of Advanced Engineering and Science, 2013)
High voltage circuit breakers play an important role in the power system. So it is necessary to implement the state detection of breakers in order to ensure stable and reliable running of the grid. The purpose of state detection is to provide reliable basis of maintenance by extracting mechanical state parameters accurately. This paper mainly focuses on the coil current signal feature extraction algorithm. To settle the problem of too much noise mixed with the current signal and signal distortion, the discrete wavelet transform algorithm is used to extract the coil current signal parameters. This paper also designs the FIR filter to extract stroke and speed parameters from travel-time waveform. The experiments show that the difference between the theoretical results and test results processed by the method in this paper is very small and the test results are able to accurately reflect operation states and mechanical features of high voltage circuit breakers. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2550